2019
DOI: 10.7150/thno.29247
|View full text |Cite
|
Sign up to set email alerts
|

A Blood-Based Multi Marker Assay Supports the Differential Diagnosis of Early-Stage Pancreatic Cancer

Abstract: The most frequent malignancy of the pancreas is the pancreatic ductal adenocarcinoma (PDAC). Despite many efforts PDAC has still a dismal prognosis. Biomarkers for early disease stage diagnosis as a prerequisite for a potentially curative treatment are still missing. Novel blood-based markers may help to overcome this limitation. Methods: Prior to surgery plasma levels of thrombospondin-2 (THBS2), which was recently published as a novel biomarker, and CA19-9 from 52 patients with histologically prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 50 publications
3
36
0
2
Order By: Relevance
“…THBS2 expression has been described previously as biomarker for patients with PDAC and has been shown to correlate with high dysplasia grade in patients with premalignant disease . Combined expression of THBS2 and CA19‐9 demonstrated comparable diagnostic accuracy to distinguish patients with PDAC from HDs and patients with BD, in line with our results . These studies reported slightly different optimal cutoff values of THBS2 (42 and 28.9 ng/mL), almost comparable to the present study (40 ng/mL).…”
Section: Discussionsupporting
confidence: 91%
“…THBS2 expression has been described previously as biomarker for patients with PDAC and has been shown to correlate with high dysplasia grade in patients with premalignant disease . Combined expression of THBS2 and CA19‐9 demonstrated comparable diagnostic accuracy to distinguish patients with PDAC from HDs and patients with BD, in line with our results . These studies reported slightly different optimal cutoff values of THBS2 (42 and 28.9 ng/mL), almost comparable to the present study (40 ng/mL).…”
Section: Discussionsupporting
confidence: 91%
“…In most of these studies, the candidate biomarker is compared with CA 19-9. Two studies investigated the diagnostic value of thrombospondin-2 (THBS2), which is a disulfide-linked homotrimetric glycoprotein that mediates cell-to-cell and cell-to-matrix interactions [128,129]. The levels of THBS2 were compared in patients with PDAC, as compared to patients with benign pancreatic diseases.…”
Section: Blood-based Protein and Metabolite Markersmentioning
confidence: 99%
“…The expression levels of circulating tissue metalloproteinase inhibitor-1 (TIMP1) and Leucine-rich alpha-2-glycoprotein 1 (LRG1), thrombospondin-2 (THBS2) showed comparable diagnostic performance to CA19-9. While the diagnosis of early PDA could be significantly improved by combining the expression of these blood molecules with CA19-9 [ 13 , 14 ]. It is worth to mention here, similar to circulating proteins, blood metabolites demonstrated diagnostic potentials to detect PDA at early stage, either alone or in combination with CA19-9 or other proteins, as exemplified by recent studies which revealed that plasma metabolites, such as acetylspermidine, diacetylspermine, indole-derivatives, and lysophosphatidylcholines could distinguish PDA from healthy subjects and benign pancreatic disorders [ 15 , 16 ].…”
Section: Tumor Circulomementioning
confidence: 99%